2017
DOI: 10.3389/fncel.2017.00343
|View full text |Cite
|
Sign up to set email alerts
|

Motor Deficits and Cerebellar Atrophy in Elovl5 Knock Out Mice

Abstract: Spino-Cerebellar-Ataxia type 38 (SCA38) is caused by missense mutations in the very long chain fatty acid elongase 5 gene, ELOVL5. The main clinical findings in this disease are ataxia, hyposmia and cerebellar atrophy. Mice in which Elovl5 has been knocked out represent a model of the loss of function hypothesis of SCA38. In agreement with this hypothesis, Elovl5 knock out mice reproduced the main symptoms of patients, motor deficits at the beam balance test and hyposmia. The cerebellar cortex of Elovl5 knock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 20 publications
4
34
0
Order By: Relevance
“…PianpKO mice, however, did not show deficits in basic motor functions. In a mouse model of spinocerebellar ataxia these tests also revealed normal results [44]. Mice, as four-legged animals, might be less sensitive to cerebellar alterations in terms of motor functions.…”
Section: Discussionmentioning
confidence: 90%
“…PianpKO mice, however, did not show deficits in basic motor functions. In a mouse model of spinocerebellar ataxia these tests also revealed normal results [44]. Mice, as four-legged animals, might be less sensitive to cerebellar alterations in terms of motor functions.…”
Section: Discussionmentioning
confidence: 90%
“…The thickness of the molecular layer correlates with the length of the PC dendritic tree [45]. To examine the approximate length of PCs’ dendrites, we measured the thickness of the molecular layer and found that it was significantly reduced by S100β (Figure 4A,B).…”
Section: Discussionmentioning
confidence: 99%
“…This gene is involved in the long-chain fatty acids elongation cycle, and it is highly expressed in Purkinje cells. Furthermore, the ELOVL5 -/- mice develop ataxia and motor impairment during the balance beam test ( Hoxha et al, 2017 ). Several neurological diseases, particularly hereditary spastic paraplegias ( Dick et al, 2010 ; Tesson et al, 2012 ; Boukhris et al, 2013 ; Martin et al, 2013 ) display alterations of lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the effect of mutant ELF2 on ATNX2 and ELOVL5 expression levels, since these genes are a direct target of ELF2, according to Curated Transcription Factor Targets Dataset (TRANSFAC), and both have been associated with SCA2 and SCA38 ( Scoles et al, 2012 ; Di Gregorio et al, 2014 ; Hoxha et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%